Complement-Coagulation Cross-talk: Factor H-mediated regulation of the Complement Classical Pathway activation by fibrin clots - Kang, Yu-Hoi; Varghese, Praveen M.; Aiyan, Ahmad Al; Pondman, Kirsten; Kishore, Uday; Sim, Robert B. (Frontiers in Immunology, 2024)
The classical pathway of the complement system is activated by the binding of C1q in the C1 complex to the target activator including immune complexes. Factor H is regarded as the key downregulatory protein of the alternative pathway of complement. However, C1q and factor H both bind to target surfaces via charge distribution patterns. For few targets, C1q and factor H compete for binding to common or overlapping sites. Factor H, therefore, can effectively regulate the classical pathway activation by such targets, in addition to its previously characterized role in the alternative pathway. Both C1q and factor H are reported to recognize “foreign” or altered-self materials, for example bacteria, viruses and damaged tissues. Clots, formed by the coagulation system, are an example of altered self. Factor H is present abundantly in platelets and is a well-known substrate for FXIIIa. Here, we investigated whether clots activate the classical pathway of complement and whether this is regulated by factor H. We show here that both C1q and factor H bind to fibrin formed in microtitre plates as well as fibrin clots formed under in vitro physiological conditions. Both C1q and factor H become covalently bound to fibrin clots and this is mediated via FXIIIa. We also show that fibrin clots activate the classical pathway of complement, as demonstrated by C4 consumption and membrane attack complex detection assays. Thus, factor H downregulates the classical pathway activation induced by fibrin clots. These results elucidate the intricate molecular mechanisms through which the complement and coagulation pathways intersect and have regulatory consequences.